2011
DOI: 10.5755/j01.mech.17.2.332
|View full text |Cite
|
Sign up to set email alerts
|

Effects of VNT and IGV association on turbocharger centrifugal compressor performances

Abstract: w-prewhirl angle, deg; 'H SF-skin friction losses; 'H P-power losses; 'H L-leakage losses; 'H DF-disc friction losses; 'H BL-blade loading losses; 'H INC-incidence losses;

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…The pressure difference gives a technical basis for studying the aerodynamical moment and frictional moment of the guidance blade. At the same time, the pressure field distribution of guidance blades was compared with the results from Izidi and Liazid [4], Luo et al [13], and Touil and Ghenaiet [26]. The accuracy of the pressure field distribution of guidance blades has been compared and verified.…”
Section: Pressure Field Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The pressure difference gives a technical basis for studying the aerodynamical moment and frictional moment of the guidance blade. At the same time, the pressure field distribution of guidance blades was compared with the results from Izidi and Liazid [4], Luo et al [13], and Touil and Ghenaiet [26]. The accuracy of the pressure field distribution of guidance blades has been compared and verified.…”
Section: Pressure Field Analysismentioning
confidence: 99%
“…At the same time, it is also concluded that the torque and power produced by asymmetric blades are greater than that of symmetric blades. Izidi and Liazid [4] studied the influence of area change on work efficiency at the exit and imported leaves. This technology improves the performance of the compressor in the whole working range.…”
Section: Introductionmentioning
confidence: 99%
“…where λ H is excess air factor at altitude H above sea level, π KH is air pressure increase rate in compressor above sea level, H > 0; π k0 = P outlet /P intlet is air pressure increase rate in the compressor at altitude H = 0 m [9]; n H is air compression polytrophic ratio in compressor. Nondimensional heat transfer characteristic (K Q ), heat amount required to vaporize and overheat a kilogram of the fuel by injection into the compressed air of the engine cylinder at temperature T C (q T ), cylinder volume at the fuel injection moment (V IP ) , fuel ignition delay (φ 1 ) and fuel rapid combustion period (φ 2 ) and cycle maximum pressure (P Z ) are calculated as follows…”
Section: Calculation Of Military Fuel Combustion Ratementioning
confidence: 99%
“…Centrifugal compressor, which is the most available highspeed turbomachinery [2], is featured in high rotational speed, centrifugal force, and stability. Exhaust flow from engine is directed over turbine blades to drive the turning of compressor and shaft.…”
Section: Introductionmentioning
confidence: 99%